Melissopalynological analysis of honey produced by two species of stingless bees in Lombok Island, Indonesia - Lalu Zulkan Jayadi; Ratna Susandarini (Nusantara Bioscience, 2020)
Abstract. Jayadi LZ, Susandarini R. 2020. Melissopalynological analysis of honey produced by two species of stingless bees in Lombok Island, Indonesia. Nusantara Bioscience 12: 97-108. Honey is a natural product with a variety of benefits that commonly used as food sweeteners, health supplements, and traditional medicine. There has been no comprehensive publication regarding the diversity of pollen contained in honey produced by stingless bee Tetragonula laeviceps and Heterotrogona itama from Lombok. This study aimed to reveal the diversity of pollen content in honey through melissopalynological analysis of honey samples produced by two species of stingless bees T. laeviceps and H. itama in Lombok Island. This melissopalynological study was performed on honey samples obtained from nine villages from nine sub-districts representing the three districts on Lombok Island. Pollen extraction from honey was carried out using standard methods for melissopalynological analysis. The diversity of pollen recovered from honey varied from 15 to 41 pollen types. Total number of plant species whose pollen was recovered from honey samples was 127 which consisted of 61 families. The occurrence of predominant pollen type in particular unifloral honey samples indicated their botanical origin and presumed geographical origin of honey. Results of this study are useful in confirming botanical origin of honey and generating information on plants potential as food source for sustainable beekeeping in Lombok Island.